Tumor cell-intrinsic PD-1 receptor is a tumor suppressor and mediates resistance to PD-1 blockade therapy - Wang, Xiaodong; Yang, Xiaohui; Zhang, Chang; Wang, Yang; Cheng, Tianyou; Duan, Liqiang; Tong, Zhou; Tan, Shuguang; Zhang, Hangjie; Saw, Phei Er; Gu, Yinmin; Wang, Jinhua; et al. (Proceedings of the National Academy of Sciences - PNAS, 2020)
The programmed cell death 1 (PD-1) receptor on the surface of immune cells is an immune checkpoint molecule that mediates the immune escape of tumor cells. Consequently, antibodies targeting PD-1 have shown efficacy in enhancing the antitumor activity of T cells in some types of cancers. However, the potential effects of PD-1 on tumor cells remain largely unknown. Here, we show that PD-1 is expressed across a broad range of tumor cells. The silencing of PD-1 or its ligand, PD-1 ligand 1 (PD-L1), promotes cell proliferation and colony formation in vitro and tumor growth in vivo. Conversely, overexpression of PD-1 or PD-L1 inhibits tumor cell proliferation and colony formation. Moreover, blocking antibodies targeting PD-1 or PD-L1 promote tumor growth in cell cultures and xenografts. Mechanistically, the coordination of PD-1 and PD-L1 activates its major downstream signaling pathways including the AKT and ERK1/2 pathways, thus enhancing tumor cell growth. This study demonstrates that PD-1/PD-L1 is a potential tumor suppressor and potentially regulates the response to anti-PD-1/PD-L1 treatments, thus representing a potential biomarker for the optimal cancer immunotherapeutic treatment.